Convenience Food : An Emerging Trend in India (Indian Journal of Public Health Research & Development, 2020)
Convenience food industry has shown a rapid growth in India in the last few years. Now a days they arevery much in demand and is growing at a rapid rate. These foods are saviour for busy and working people.They have been widely accepted by the non-working people as well. Due to fast and busy life, consumptionpattern of people is drifting from raw food to convenience foods. Convenience foods are overly processedfood which saves the preparation and cooking time of food in the kitchen.. Young generation children aremore likely to consume packaged food as they give great aroma, texture and taste. These foods determinethe food choices and consumption pattern of the consumers. Urbanisation and the changing lifestyle has ahuge role in increasing the demand of such food items. They are gaining immense popularity in the foodindustry, global food market and among the food scientists. In the past few years convenience food hasshown a remarkable growth in the food market . This present study aims at studying the consumption patternof convenience food in India.
Keywords: Food choice, Packaged food , Saviour, Lifestyle, Growth, Consumption pattern, India